Internal audit integration with risk management: a comprehensive bibliometric analysis (1990-2023) - Jaber, Taha Ahmad; Shah, Sabarina Mohammed; Mustapha, Mazlina; Johari, Jalila; Ali, Furman (Inderscience Publishers, 2026)
This study explores the 'state-of-the-art' scientific literature related to internal audit (IA) coupled with risk management (RM) and/or enterprise risk management (ERM). Data from Scopus and Web of Science (WoS) databases was systematically collected using targeted keywords. Systematic reviews and bibliometric analyses were conducted through the preferred reporting items for systematic reviews and meta-analyses (PRISMA) and biblioshiny methods, respectively. The findings reveal that publications related to IA coupled with RM and/or ERM began in the early 1990s and have notably expanded in the past decade. Collaborative research primarily involves two authors, with USA, Romania, and UK exhibiting the highest publication numbers in the domain. Previous research has focused on interactions among four main areas, and four specific related themes have been identified. This study represents one of the first bibliometric analyses in the domain, covering the years 1990 to 2023, and establishes a foundational framework for future research.